A comparative study of marital horizons between college students and workers - Pinasthika Kautsari Pradipta; Langgersari Elsari Novianti; Yuliana Hanami; Fredrick Dermawan Purba (Personifikasi: Jurnal Ilmu Psikologi, 2026)
Marriage is an important developmental task during emerging adulthood. However, individuals may differ in how they perceive marriage; this may depend on their life stage and social role, particularly between college students and working adults. This study aimed to examine differences in marital horizons in terms of employment status. A total of 499 adults aged 18–29 years, consisting of college students and working adults, participated in this study through convenience sampling. A quantitative comparative design was employed, and data were collected using the Criteria Marriage Readiness Questionnaire (CMRQ). The results indicated significant differences in marital horizons between the two groups. College students tended to view marriage as a long-term goal that could be postponed until various aspects of readiness were fulfilled, whereas working adults perceived marriage as a more immediate and realistic commitment. Despite these differences, both groups demonstrated similar views regarding essential qualities for marriage, including commitment, responsibility, emotional maturity, communication skills, and interpersonal competence. These findings suggest that marital horizons are influenced not only by chronological age but also by individuals’ developmental transitions and engagement in adult responsibilities. Overall, marriage is perceived not only as a marker of adulthood but also as a long-term commitment that requires multidimensional readiness.